Implementation of the Waterfall for Web-Based Integrated Network Service Management System: WiFi, CCTV, Cable TV - Vivit Ardiansyah; Soffiana Agustin (Jurnal Ilmiah Sistem Informasi, 2026)
The management of integrated network services, including WiFi, CCTV, and Cable TV, requires high data accuracy to ensure customer satisfaction and revenue stability. PT. Sumber Aiti faced operational challenges due to manual administrative systems, causing data redundancy, delays in handling service disruptions, and financial discrepancies in the billing cycle. This study aims to design and develop a Web-Based Integrated Network Service Management Information System using the Waterfall development method. The Waterfall method was selected for its structured, sequential phases, requirements analysis, design, implementation, testing, and maintenance, which align with PT's stable, procedural business processes. Sumber Aiti. The system integrates customer registration, service monitoring, and automated billing management (e-billing). Functional testing using Black Box Testing on 11 test scenarios showed that 10 of 11 features (90.9%) functioned correctly, including authentication, service registration, payment processing, and administrative reporting. Comparative analysis of business processes indicates that the system reduces manual recording steps from 7 to 3 stages (57% reduction) and eliminates data redundancy across WiFi, CCTV, and Cable TV service records. The implementation of this system provides a strategic solution for improving operational efficiency and administrative accountability at PT. Sumber Aiti.